Economic Development in Turkey Stabilizes: Banking Sector Reforms Make Progress - Alfred Steinherr; Joachim Volz (Weekly Report, 2005)
The year 2004 saw Turkey take a big step forward to the European Union, as international investors also believe, and in December last year the European Council opened up real prospects of entry for Turkey for the first time. Agreement was also reached with the International Monetary Fund (IMF) on further support, chiefly to secure the servicing of public debt in the next few years. The consequences of the serious financial crisis in 2001 now seem to be largely overcome, although the inflation rate is still too high - currently at around 9%. However, it is believed that Turkey may well fulfil the Maastricht criteria for public budgets in the next two years. According to the latest figures economic growth was around 9% last year, and strong growth is expected this year as well. This analysis takes a closer look at some of the important aspects of Turkey's economic development in recent years and the state of the reforms already carried out, particularly in the banking sector. It shows that the Turkish economy is developing very satisfactorily - compared with the development in the most recent new EU member states as well, so at least in the economic perspective Turkey's aim of coming close to EU membership in the medium term does not appear to be unrealistic.
Keywords: 330